The impact of socio-economic factors on the health of the Moroccan immigrants in Navarra (Spain) - Montoro-Gurich,Carolina (2018)
This paper analyses from a perspective the social determinants, socio-demographic and lifestyle factors that affect the health self-appraisal of immigrants of Moroccan origin living in the Spanish region of Navarra, using data from a cross-sectional ethnosurvey conducted in 2013. Results show, contrary to the literature, that women have a better health status variation than men, probably because men have a higher age profile and a longer stay in Spain. The binary logistic regression reveals important differences in the likelihoods of finding specific determinants of the health by sex. Paid employment is the most positive, significant factor for health among women. Close social ties with other Moroccan immigrants, living in an inexpensive old house and, to a lesser extent, having a secondary level of educational achievement show the highest probabilities for men.